Green Marketing: A Comprehensive Bibliometric Analysis and Current Trends - Tengiz Taktakishvili; Nino Sachaleli (European Scientific Journal, ESJ, 2025)
In recent years, there has been a growing interest in green marketing research that can be traced through the abundance of published literature on the topic. However, there is still a lack of comprehensive and systematic research focusing on the evolution of this field. The main objective of this paper was to consolidate the state-of-the-art research on green marketing through a bibliometric study of articles published from 2014 to 2024 and to analyze and present the results. According to the research it was found out that green marketing is a trend nowadays and its citation index, as well as several articles, is growing rapidly.  The analysis shows that sustainability-focused topics such as green marketing, sustainable development, and consumption behavior are on the rise, with key discussions peaking around 2022. These trends are reshaping industries and consumer habits. While supply chain management and decision-making may have started earlier, the overall picture reveals a growing commitment to sustainability that is becoming central to business strategies and consumer choices. This trend is likely to continue, and the focus on sustainability will only become more important in the coming years.